PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE PADA MATERI KERAGAMAN BUDAYA DAN KEARIFAN LOKAL SISWA KELAS IV MI NURUL HUDA SAWO - Nikmatul Azizah, Mila; Miftahul Munif, Moh. Vito (Fakultas Agama Islam, 2026)
This study aims to describe the implementation of the cooperative learning model take and give in the subject matter of cultural diversity and local wisdom, and to analyze the activeness of fourth grade students at MI Nurul Huda Sawo during the learning process. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings revealed that the implementation of take and give consisted of three stages: preparation, implementation, and closing. The teacher prepared learning cards, and students studied and exchanged information with peers. This process created an interactive, enjoyable, and participatory learning atmosphere. Students’ activeness increased significantly, as reflected in their willingness to ask, answer, and express opinions. Observation data showed that most students were categorized as active to very active, with activeness percentages ranging from 72% to 92%. These findings suggest that take and give effectively enhances student activeness while reducing teacher dominance. Thus, it is relevant to be applied in IPAS learning, particularly in cultural diversity and local wisdom materials